Aksiologi Ilmu dalam Konteks Ilmu Pengetahuan: Systematic Literature Review - Lezi, Kusma (Journal of Innovation in Teaching and Instructional Media, 2025)
Axiology of science is a branch of philosophy of science that is very important in the development of science because branches of science that do not have axiological value can bring harm to humans. The aim of this research is to analyze the relationship between scientific axiology and science. This research uses the systematic literature review (SLR) method by searching for journals that are relevant to the research objectives. In this research there are 15 journals that are relevant to the research questions and objectives. The research results show that axiology provides a solid foundation for developing knowledge related to moral and ethical aspects. Axiology has a huge influence on someone to apply the knowledge they have without harming others, to behave morally, to aestheticize science.